Tax Reform and Investment Decision Effects in an Emerging Economy: Insights from Ghana - YEBOAH, Michael; DANQUAH, Benjamin Adjei; BAWUAH, Jonas; NKWANTABISA, Agyeiwaa Owusu (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).05, 2025)
This study focuses on both domestic and foreign investment as indicators of economic growth in an emerging market context, examining the effects of tax reforms on investment decisions in Ghana from 1985 to 2020. The research employs a time-series analysis to integrate control variables like inflation, gross capital formation, and base rate, revealing their significant influence on investment activity in tandem with tax policy changes. Unlike previous research that mostly uses gross fixed capital formation as a proxy for investment, this study includes a wider range of investment types, giving a more complete picture of how the economy works. We did unit root and co-integration tests, which showed that the variables were first-order co-integrated. We performed the model estimate using a Vector Error Correction Model (VECM) and Granger causality tests. Results reveal that tax reforms have a measurable impact on investment patterns, underscoring the importance of adaptive tax policies in promoting sustainable economic development. The findings contribute to the broader literature on investment and fiscal policy in emerging economies, offering insights for policy-makers on optimizing tax strategies to encourage investment and drive economic growth.